2019
DOI: 10.1038/s41598-019-46957-4
|View full text |Cite
|
Sign up to set email alerts
|

Achieving excellent microformability in aluminum by engineering a unique ultrafine-grained microstructure

Abstract: During microforming of conventional materials, specimen and microstructural length-scales are close to each other. This leads to an abnormal deformation behavior of the material and reduces microformability. Engineering ultrafine-grained (UFG) microstructure in the material is a possible solution. However, micro-scale deformation behavior of UFG material is not fully understood. Present work attempts to comprehensively investigate the micro-scale deformation of four distinctly engineered microstructures: UFG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A study 40 reported that the grains are elongated in the highly stressed cup region. However, when the initial grain size is already elongated, there is no appreciable change in grain length at the length scale of 250 microns.…”
Section: Resultsmentioning
confidence: 99%
“…A study 40 reported that the grains are elongated in the highly stressed cup region. However, when the initial grain size is already elongated, there is no appreciable change in grain length at the length scale of 250 microns.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out above, the activation of dislocation sources contributes to dislocation generation. Cold deformation can promote the transformation of equiaxed grains into elongated ones, and grain boundary-mediated plasticity can result in stress-assisted grain growth because of the migration, rotation, and coalescence of the grains in a preferred direction for accommodating the strain paths [45,46]. Besides, the formation of slip bands in the grains is evident, eventually revealing the localization of plastic deformation [47].…”
Section: Complete Tensile Testmentioning
confidence: 99%
“…TEM analysis points to the presence of a high density of DTs. In materials being characterized by facilitated cross slip, as is the case for cp-Fe, the formation of DTs and further LAGBs can occur [46]. Eventually, in cases of intense dislocation motion at higher strains, barriers that initially require low energy to be overcome by dislocations can consolidate, evolving into grain boundaries of low misorientation angle, and finally resulting in HAGBs at the highest deformations (if localized cracking does not set in earlier).…”
Section: Process-microstructure-property-relationshipsmentioning
confidence: 99%
“…Rosochowski et al already showed in 2007, by using micro-cup extrusion tests, that the use of nano-crystalline microstructures can improve the homogeneity of the material flow and the surface quality in bulk microforming processes [13]. Dahl et al have proven in deep drawing tests that compared to conventional grain structures, the use of nano-crystalline grain structures can significantly improve the surface quality, the dimensional stability and the process scattering in micro sheet forming [14]. Thus, the microstructure of the material AA6014 is modified to this state by using an accumulative roll bonding (ARB) process.…”
Section: Introductionmentioning
confidence: 99%